From global poverty to global equality a philosophical exploration - Gilabert, Pablo (Oxford : Oxford University Press, 2012)
'From Global Poverty to Global Equality' provides a philosophical exploration of some of the central questions in the flourishing debate on global justice: Do we have a duty to help eradicate global poverty? Do we also have a duty to pursue global equality? What makes such demands morally justifiable?
Includes bibliographical references and index.
Description based on print version record.
Keywords: Equality; Distributive justice; Poverty -- International cooperation; Globalization -- Social aspects; International relations -- Moral and ethical aspects